The Morale for Job Performance of Teachers in the Secondary Educational Service Area Office Ubon Ratchathani Amnat Charoen - Pahpapha, Phermyot; Jantahin, Thidarat; Masena, Chuankid (Journal of Roi Et Rajabhat University, 2023)
The purposes of the research were 1) to study the morale for job performance of teachers in schools, 2) to compare levels of the morale for job performance of teachers in schools, and 3) to study the guidelines for enhancing the morale for job performance of teachers in schools in the Secondary Educational Service Area Office Ubon Ratchathani Amnat Charoen. The samples included school administrators and teachers under the Office of Secondary Education Service Area, Ubon Ratchathani, Amnat Charoen, consisting of 478 persons by stratified sampling. The target groups for in-depth interviews were 4 school administrators or teachers who received awards by purposive sampling. The research tools were a 5-level rating scale questionnaire and a structured interview form. The data were analyzed by using percentage, mean, standard deviation, t-test, and F-test. The research findings were as follows: 1) A study of the morale for job performance of teachers in schools under the Office of Secondary Education Service Area, Ubon Ratchathani, Amnat Charoen by overall aspects at a high level 2) Comparison of the morale level of teachers in schools under the Office of Ubon Ratchathani Secondary Education Service Area, Amnat Charoen classified by position, work experience, and school size found that the overall performance was a statistically significant difference at the .01 level. 3) Guidelines for enhancing the morale for job performance of teachers in schools in the Secondary Educational Service Area Office Ubon Ratchathani Amnat Charoen as follows; 1) Salary and welfare should be fair, 2) Working environment and atmosphere, place and environment should be developed, 3) Relationship with colleagues, promote relationship-building activities, 4) Various policies in operation should focus on participation, 5) Operational success should be positive reinforcement, 6) Responsibility in the job, encouraging to work together as a team, and 7) Progress in work, support for professional advancement.